Ventilation Homogeneity Improves with Growth Early in Life - Chakr, Valentina C. (2011)
Some studies have suggested that lung clearance index (LCI) is age-independent among healthy subjects early in life, which implies that ventilation distribution does not vary with growth. However, other studies of older children and adolescents suggest that ventilation becomes more homogenous with somatic growth. We describe a new technique to obtain multiple breath washout (MBWO) in sedated infants and toddlers using slow augmented inflation breaths that yields an assessment of LCI and the slope of phase III, which is another index of ventilation inhomogeneity. We evaluated whether ventilation becomes more homogenous with increasing age early in life, and whether infants with chronic lung disease of infancy (CLDI) have increased ventilation inhomogeneity relative to full term controls. Fullterm controls (N = 28) and CLDI (N = 22) subjects between 3 and 28 months corrected-age were evaluated. LCI decreased with increasing age; however, there was no significant difference between the two groups (9.3 vs. 9.5; p = 0.56). Phase III slopes adjusted for expired volume (S(ND)) increased with increasing breath number during the washout and decreased with increasing age. There was no significant difference in S(ND) between fullterm and CLDI subjects (211 vs. 218; P = 0.77). Our findings indicate that ventilation becomes more homogenous with lung growth and maturation early in life; however, there is no evidence that ventilation inhomogeneity is a significant component of the pulmonary pathophysiology of CLDI.